Microbiological Etiology of Chronic Skin Lesions in Type 2 Diabetic Subjects - Chisari, Giuseppe; Chisari, Laura M.; Borzì, Antonio M.; Luca, Salvatore; Grasso, Antonino; Chisari, Clara G. (Infectious Disorders - Drug Targets, 2019)
Introduction: Skin lesions represent lesions that result in loss of tissues and their joints and often this cutaneous process is a primary or secondary consequence of structural changes in the same skin surface. Type 2 diabetic subjects developing chronic skin lesions in the lower limbs in the western world are steadily increasing. We conducted a study on the etiologic incidence of chronic skin lesions in type II diabetic subjects in the lower limbs compared to subjects with chronic skin lesions (controls). Materials and Methods: Thirty subjects (group
Keywords: positive culture